ACL reconstruction using a bone patellar tendon bone (BPTB) allograft or a hamstring tendon autograft (GST): a single-center comparative study - Biz, Carlo; Cigolotti, Augusto; Zonta, Filippo; Belluzzi, Elisa; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: There is still debate on which graft is better indicated for anterior cruciate ligament (ACL) surgical reconstruction. The objective of this study was to evaluate the medium-term clinical outcomes of ACL reconstruction comparing patients managed with bone patellar tendon bone allograft (BPTB) versus patients treated with hamstring autograft (GST). Methods: Patients enrolled during the period 2013-2016 underwent a personal interview with the use of specific evaluation questionnaires (Tegner e Lyshom, Knee Injury and Osteoarthritis Outcome Score, International Knee Documentation Committee), a clinical evaluation with the use of objective functional tests (Lachman test, pivot-shift) and a physical examination of the knee. Results: In this study 43 patients were enrolled: 21 patients were treated by autograft and 22 patients by allograft. Patients who received allograft ACL reconstruction returned to normal sport activity earlier than patients operated on using autograft (11.7±10.3 vs 17.9±14.6 weeks, p<0.05). Data obtained with subjective tests, clinical and physical examination were positive overall, with no differences observed between the two groups. Finally, 15 allograft patients and 12 autograft patients accepted to perform the proprioceptive tests: no difference was found between the two groups. Conclusions: At follow-up evaluation after ACL reconstruction, both BPTB allograft and GST autograft patient groups showed similar results at subjective, objective clinical evaluation and proprioceptive properties of the limb. In particular, the use of allogenic BPTB allowed the patients to return earlier to normal activities of daily-living and sport activity.